The Effects of Millennial Behavior and Perceptions on Interest in Sharia Mobile Banking and the Implications of Continuance Intention - Yasmin, Azura; Sarmigi, Elex; Putra, Eka (BISNIS, 2024)
This research aims to determine the behavior and perceptions of the millennial generation towards sustainable use (continuance intention) both directly and when mediated by interest. This research uses a quantitative approach method by collecting data using an online questionnaire using Google Forms and distributing the questionnaire via social media. The research population was the millennial generation who used Syariah mobile banking, with 111 respondents. The collected data was then analyzed using Structural Equation Modeling (SEM) with the help of the smarts application. The results of this study show that the influence of interest in continuous intention and millennial perception significantly influence interest in using Syariah mobile banking. In contrast, financial and online behavior does not directly impact the constant use (continuance intention) of Syariah mobile banking and the influence of economic behavior on interest. Also not significant, the results of hypothesis testing prove that millennial perceptions influence continuance intention (sustainable use), which is mediated by interest (sustainable use). In contrast, financial and online behavior, mediated by interest, do not affect continuance intention.